93 Does Intervention of Severe Valve Lesions always Improve Cardiac Function?. (6th June 2015) - Hothi, Sandeep; Tan, David; MacDonald, Wanda; Tan, Lip Bun; Schlosshan, Dominik
Abstract : Introduction: Severe valve lesions can result in cardiac decompensation. This study investigated the effects of surgical valvular intervention upon cardiac function assessed as peak cardiac power output (CPOmax ) generation during exercise. We hypothesised that (i) cardiac function improves after valvular intervention, and (ii) those with subnormal pre-operative cardiac reserve indicative of cardiac decompensation would gain less physical and cardiac functional benefits than those with preserved pre-operative cardiac function. Methods: We compared the cardiopulmonary exercise performance and non-invasive haemodynamics of 46 consecutive patients with severe valvular disease before and after valvular intervention with reference to 101 healthy male and 139 female controls without cardiovascular disease. Cardiac and physical functional reserves were measured with standard respiratory gas analyses and CO2 rebreathing to measure peak cardiac output and quantify peak cardiac power output (CPOmax ) non-invasively during treadmill exercise. Data are given as mean±SD and statistical significance accepted at P < 0 .05. Results: The patient cohort showed no overall benefit from valvular intervention (pre-operative CPOmax 3.48 ± 1.27W, post-operative CPOmax 3.60 ± 0.96W, P = 0.42, n = 4 6). However, this comprised opposing effects upon two subgroups distinguished by a pre-operative CPOmax below (LoW subgroup) or within (HiW subgroup) the normal range defined by the control population. Thus, in the LoW subgroup CPOmax increased with valvular intervention from 2.63 ± 0.67 to 3.42 ± 0.98W (P = 0.000014; n = 2 6), NYHA class improved (from 2.29 ± 0.75 to 1.65 ± 0.75, P = 0.0004), peak oxygen consumption (VO2max ) increased (from 1.38 ± 0.55 to 1.56 ± 0.59 l.min -1, P = 0.002), and peak flow- and cardiac pressure-generating capacities increased. In contrast, in the HiW subgroup, CPOmax decreased from 4.58 ± 0.96 to 3.84 ± 0.92W following intervention (P = 0.00026; n = 2 0). NYHA classification remained unchanged, VO2max decreased (from 2.29 ± 0.72 to 1.97 ± 0.75 l.min -1, P = 0.005) and peak cardiac flow- and pressure-generating capacities significantly decreased (all P < 0.05) after valve intervention. Conclusions: This is the first investigation of the effects of surgical intervention upon non-invasively measured CPOmax during exercise in patients with severe valvular disease. It unexpectedly demonstrates that valvular interventions performed in routine clinical practice do not consistently improve cardiac function. Patients with subnormal pre-operative cardiac functional reserve benefited from intervention, with significantly improved cardiac and physical fitness. Patients with normal pre-operative cardiac functional reserve generally showed decreased cardiac and physical fitness.